EFFECTS OF DIFFERENT PACKAGING MATERIALS ON THE KEEPING QUALITY OF KULIKULI (FUDMA JOURNAL OF SCIENCES, 2024)
The effects of different packaging materials: plastic material, aluminium foil, glass material, low density polyethylene bag (LDPB) and a blend of plastic materials and LDPB on the keeping quality of kulikuli was studied. The quality indices studied were peroxide value, free fatty acid, saponification value and sensory attributes using standard methods. The results of the study showed that at the end of first week of storage, stored snacks exhibited different variabilities in the quality parameters measured. Snacks stored in foil paper and in a blend of plastic and LDPB had significantly (p
Keywords: Groundnut; Kulikuli; Packaging material; Keeping quality